Structuring Building Information for Cost Control: A Case Study of BIM in the Housing Production - Melin, Isabelle; Persson, Josefin (My University, 2022)
Construction projects have for a long time been characterized by sub-optimization and fragmented information exchange, resulting in inefficient production control and cost overruns. Cost control represents an important part of taking appropriate actions to keep the budget on track. Research within the context of cost control and Building Information Modeling (BIM) has discussed how it can facilitate early phases of construction projects. However, limited attention has been on BIM benefits and its requirements for cost control in the construction phase. The aims of this thesis were to identify how BIM can facilitate cost control and to determine the requirements that need to be established for information and model in the housing production. Semi-structured interviews were conducted with 13 support functions and 11 site management respondents at a contractor company in Sweden. Results show that BIM can be used as a decision-making platform to facilitate information take-off for cost control, as in filtration, comparison, and visualization of multidimensional information. Furthermore, for supporting cost control in the housing production, BIM guides are required to inform all concerned stakeholders about the requirements on information and model, such as a common structure and level of development. Altogether, BIM can contribute to proactive cost control, making the cost control activities easier and more efficient. Finally, the findings can promote contractors’ strategic work to develop new and innovative cost control methods in the construction phase.
Keywords: Building Information Modeling, BIM, Cost Control, Construction Phase, Housing Production, Information Structure, Visualization, Information Take-Off, Level of Development, LOD